Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1288/00005537-198403000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Cinegraphic observations of laryngeal function in parkinson's disease

Abstract: Thirty-two unselected male patients with Parkinson's disease were examined by telescopic cinelaryngoscopy. Correlation of vocal abnormality and general neurologic symptoms with the laryngoscopic examination leads to the conclusion that the phonatory abnormalities noted in Parkinson's disease are related to rigidity in the phonatory posture of the larynx. The described dysfunctions correlated with the symmetry of trunk and limb rigidity in 100% of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 5 publications
3
86
0
4
Order By: Relevance
“…The main symptoms of PD are tremor, rigidity and other general movement disorders. Of particular importance to this study, vocal impairment is also common [10,11], with studies reporting 70-90% prevalence after the onset of the disease [11][12][13]. In addition, it may be one of the earliest indicators of the disease [14,15], and 29% of patients consider it one of their greatest hindrances [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main symptoms of PD are tremor, rigidity and other general movement disorders. Of particular importance to this study, vocal impairment is also common [10,11], with studies reporting 70-90% prevalence after the onset of the disease [11][12][13]. In addition, it may be one of the earliest indicators of the disease [14,15], and 29% of patients consider it one of their greatest hindrances [13].…”
Section: Introductionmentioning
confidence: 99%
“…Behrman, Abramson, and Myssiorek (2001) found that 60% of individuals with a diagnosis of presbylarnygeal dysphonia (voice problems due to an aged larynx) presented with glottal gaps. Second, individuals with PD often present with increased glottal gap (Blumin, Pcolinsky, & Atkins, 2004; D. G. Hanson, , & Ward, 1984;Midi et al, 2008). The present findings show individuals with PD utilize glottal approximation at maximal closure to the same degree as their healthy peers when increasing intensity, but that the mechanisms for changing MinFlow with increasing SPL may differ in people with PD as compared to HOA.…”
Section: Discussionmentioning
confidence: 62%
“…In producing breathy phonation, these speakers usually demonstrated a gap through the cartilaginous glottis, which may extend continuously through some or all of the membranous glottis (Holmberg et al, 1988;S€ odersten and Lindestad, 1990). However, speakers with voice disorders may have a gap that appears only in the membranous glottis, as occurs in presbylaryngis (the aged larynx) or in some patients with Parkinson disease who have breathy voices (Hanson et al, 1984). Because this glottal configuration was not included in our study, it is possible that AC/OQ may not measure these voices adequately.…”
Section: Discussionmentioning
confidence: 99%